FACTORS AFFECTING AGRICULTURAL TEACHERS’ WORK ATTITUDE IN SELECTED SECONDARY SCHOOLS: A CASE OF ABEOKUTA-SOUTH AND SAGAMU LOCAL GOVERNMENT AREAS, OGUN STATE, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2023)
This study assessed the relationship between agricultural teachers’ socioeconomic characteristics and their work attitude. A structured questionnaire was used to elicit information from a total of 96 agricultural teachers in selected secondary schools in Abeokuta South and Sagamu Local Government Areas of Ogun State, through a multi-stage sampling procedure. The data collected were subjected to descriptive, Pearson Product Moment Correlation (PPMC) and Chi square analyses. Results indicated that 61.3% of the agricultural teachers were females, with modal (49.6%) age between 41 and 50 years. Majority (73.0%) were married and 59.1% held the position of class teacher. In terms of work attitude, results showed that agricultural teachers exposed students to both theory and practical aspects of agriculture ( = 4.53 SD= 0.58) and at times used local languages to drive home important points ( =4.24, SD =0.87). Also, results revealed significant association between agricultural teachers’ work attitude and their sex (r = -0.230, p
Keywords: Work attitude, Agricultural teachers, Secondary schools, Nigeria